Management Strategies Used by Thai Postpartum Women with Maternity Blues - Phuangprasonka, Rachada; Deoisre, Wannee; Chunlestskul, Kanoknuch (Journal of Food Health and Bioenvironmental Science, 2018)
Maternity blues is a group of symptoms of mood change in early puerperium. Woman who experience maternity blues may be at an increased risk for postpartum depression. The purpose of this study was to explore the management strategies used by Thai postpartum women with maternity blues. A qualitative method, which examines subjects that are experiencing postpartum blues. A sample of 20 maternity blues women during the first 7 day after delivery were recruited and in-depth interviews were conducted to conclude the thematic and details of management strategies used by Thai postpartum women with maternity blues by content analysis. The postpartum women used the strategies to decrease maternity blues symptoms appropriately. The strategies began when the women perceived the maternity blues symptoms, and tried to manage their symptoms. The management strategies used by the participants in this study indicated five themes, which are (1) Vent feelings, (2) Relaxing activities, (3) Self-encouragement, (4) Finding helps and (5) Information seeking. The postpartum women with maternity blues needed help by the wise person. The importance to helping a maternity blues woman through this period is consistent support from social, especially family members. Furthermore, maternity blue women tried to manage their symptoms by using a varied of strategies. After participants used a strategy what follows is a contribution to overcome maternity blues experience and to enjoy and build support for the role of the mother as well.